METODE RASULULLAH DALAM PENGAJARAN SPEAKING - Happy Sri Rezeki Purba (Al-Muaddib : Jurnal Ilmu-Ilmu Sosial & Keislaman, 2016)
Prophet Muhammad SAW is the greatest person that inspired all people in the world by his methods in teaching. The major points of these methods are love and solution thathe offered to all of his students.Particularly in teaching speaking, there are six methods that lecturer can apply in facing the introvert students, they are: (1) exemplary method, (2) systematic method, (3), Discussion Method, (4),Experimental Method, (5) Situational Method, (6) award and punishment method. Through theseall methods, it hopes that the introvert student who is close, shy and quiet person can speak freely and active in the class especially in speaking class.